Variability in NGC 3201 giant stars and its impact on their spectroscopic [Fe/H] determination - Llancaqueo Albornoz, Álvaro (2021)
We present the analysis of 34 light curves in V and I of 17 giant stars in the globular cluster NGC 3201 to check if such stars are variable and if their variability has some kind of impact on the iron abundance as obtained from spectroscopic measurements. First, we computed the generalized Lomb-Scargle and phase dispersion minimization periodograms of the sample to check if the stars were variables. In this way, seven stars of the sample were found to be nonvariable, two stars are considered as possible variables, and eight stars were found to be variable, with periods ranging from 0.0881 ± 0.0001 to 0.5418 ± 0.0027 days. According to the literature, the variables have distinct values of [Fe I/H]: the three most metal-rich stars are in the red giant branch (RGB) stage, one has [Fe I/H] = -1.37 dex, while the other two have [Fe I/H] = -1.31 dex. The two most metal-poor variables have [Fe I/H] = -1.61 dex and [Fe I/H] = -1.62 dex, and are AGB stars; the remaining variables have [Fe I/H] = -1.44, -1.48, and -1.50 dex, the first two being RGB stars while the last is an AGB star. On the other hand, stars that appear to be nonvariable have -1.56 ≤ [Fe I/H] ≤ -1.40. We conclude that variability somehow affects the spectroscopic determination of the iron content of giant stars in NGC 3201, increasing the iron spread of the cluster. If variability is not taken into account, this spread could be incorrectly interpreted as due to an intrinsic iron spread affecting the stars of the cluster.